Loading of Primary Human T Lymphocytes with Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles Does Not Impair Their Activation after Polyclonal Stimulation - Mühlberger, Marina; Unterweger, Harald; Band, Julia; Lehmann, Christian; Heger, Lukas; Dudziak, Diana; Alexiou, Christoph; Lee, Geoffrey; Janko, Christina (Cells, 2020)
For the conversion of immunologically cold tumors, characterized by a low T cell infiltration, into hot tumors, it is necessary to enrich T cells in the tumor area. One possibility is the use of magnetic fields to direct T cells into the tumor. For this purpose, primary T cells that were freshly isolated from human whole blood were loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate). Cell toxicity and particle uptake were investigated by flow cytometry and atomic emission spectroscopy. The optimum loading of the T cells without any major effect on their viability was achieved with a particle concentration of 75 mu g Fe/mL and a loading period of 24 h. The cellular content of SPIONCitrate was sufficient to attract these T cells with a magnet which was monitored by live-cell imaging. The functionality of the T cells was only slightly influenced by SPIONCitrate, as demonstrated by in vitro stimulation assays. The proliferation rate as well as the expression of co-stimulatory and inhibitory surface molecules (programmed cell death 1 (PD-1), lymphocyte activation gene 3 (LAG-3), T cell immunoglobulin and mucin domain containing 3 (Tim-3), C-C motif chemokine receptor 7 (CCR7), CD25, CD45RO, CD69) was investigated and found to be unchanged. Our results presented here demonstrate the feasibility of loading primary human T lymphocytes with superparamagnetic iron oxide nanoparticles without influencing their viability and functionality while achieving sufficient magnetizability for magnetically controlled targeting. Thus, the results provide a strong fundament for the transfer to tumor models and ultimately for new immunotherapeutic approaches for cancer treatment.
CRIS-Team WoS Importer:2020-04-21